Dynamic behavior of reinforced soil retaining structures - Öztürk, T. E.; Güler, E. (Видавництво Львівської політехніки, 2011)
In this study, a parametric study of seismic response analysis of reinforced soil retaining structures was performed using finite element analysis. The aim of the study is to determine the influence of reinforcement length, reinforcement spacing, wall height and facing block width and weight on seismic-induced permanent displacements. Permanent displacements under earthquake loading conditions associated with different L/H ratios and reinforcement spacing for different wall heights varying between 2 m to 10 m are investigated. 20 seconds of Sakarya earthquake was applied in dynamic analysis to understand the response of the reinforced soil retaining walls subjected to an earthquake.
Динамічна поведінка армованих підпорних стін
Keywords: Finite Element Analysis; geosynthetics; reinforced soil; modular block; retaining wall